The impact of working capital management on firm profitability: Empirical evidence from the Polish listed firms - Sorin Gabriel Anton; Anca Elena Afloarei Nucu (Journal of Risk and Financial Management, 2021)
The purpose of this study is to investigate the relationship between working capital and firm profitability for a sample of 719 Polish listed firms over the period of 2007-2016. The scarcity of empirical evidence for emerging economies and the importance of working capital efficiency motivate the research on the working capital-financial performance relationship. The paper adopts a quantitative approach using different panel data techniques (ordinary least squares, fixed effects, and panel-corrected standard errors models). The empirical results report an inverted U-shape relationship between working capital level and firm profitability, meaning that working capital has a positive effect on the profitability of Polish firms to a break-even point (optimum level). After the break-even point, working capital starts to negatively affect firm profitability. The study brings theoretical and practical contributions. It extends and complements the literature on the field by highlighting new evidence on the non-linear interrelation between working capital management (WCM) and corporate performance in Poland. From the practitioners' perspective, the results highlight the importance of WCM for firm profitability.
Keywords: 330; emerging economy; profitability; working capital management